Effects of Children’s Communication Disorders on the Quality of Life of Their Parents in Iran - Seyed Abolfazl Tohidast; Rezvaneh Nahidi; Banafshe Mansuri; Masoomeh Salmani (Iranian Rehabilitation Journal, 2024)
Objectives: Communication disorders in children can change the parents’ lives. Some quantitative studies have investigated the effects of children’s disorders on parents’ quality of life (QoL) using questionnaires. These quantitative studies cannot comprehensively determine the extent of the impacts of such disorders in children on parents’ QoL. Quantitative studies have investigated the QoL using a few limited questions. However, qualitative studies can explore aspects of reality using a full, comprehensive, and in-depth way that may not be quantified by questionnaires. Therefore, this study qualitatively explains the effects of communication disorders in children on parents’ QoL. Methods: In this original research, 14 parents who had children with communication disorders consented to participate in semi-structured interviews. The participants were selected purposefully and the sampling was continued until the data was saturated. The interviews were transcribed and then analyzed through qualitative content analysis. Results: Qualitative content analysis of the interviews extracted five main themes, including physical effects, psychological effects, economic effects, family dynamics effects, and job-educational effects. Each of these themes consists of several subthemes. Discussion: The study revealed the depth of the negative influences of children’s communication disorders on the parents’ QoL. Screening for parental QoL and providing family support systems for parents of children with communication disorders are warranted based on these findings. Moreover, the findings of the current study can be used for the development of new instruments for measuring QoL or caregiver burden among parents of children with communication disorders.